The Application of Plant Growth Promoting Rhizobacteria Technology to Increase Peanut Production in Poor Farmers "Sumber Hidup" Farmer Group of Sigerongan Village - Hemon, A. Farid; Ujianto, Lestari; Yakob, Uyek Malik (Unram Journal of Community Service, 2024)
Some members of “Sumber Hidup” farmer group were poor farmers, farming on narrow land with low productivity. The aim of this activity was to help farmer group through the application of Plant Growth Promoting Rhizobacteria (PGPR) technology to increase peanut production on narrow land. These activities have been carried out to apply science and technology, as direct training/counseling and plot demonstrations (action research) to farmers. The method used in training was adult education with participatory techniques. Training and plot demonstration activities aimed to increase the skills and knowledge of farmers. The demonstration plot that has been carried out was in the form of action research based on the results of previous research. The demonstration plot that carried out was to compare the planting of several peanut lines using PGPR. The results of the activity showed that members of the "Sumber Hidup" farmer group were very responsive to community service activities. Farmers heard and asked the several questions related to planting superior varieties and implementing PGPR. Participants were very active in every activity such as selecting seeds, making plot demonstration, planting, hilling, weeding and harvesting activities. The technological transformation process for the use of superior varieties and the application of PGPR on narrow land has occurred in the "Sumber Hidup" farmer group. The results of the plot demonstration showed that the application of PGPR on the G19-UI groundnut line produce 3,280 g of dry pods/plot or the equivalent of 8 tonnes/hectare